SARS-CoV-2 Recombinants: Genomic Comparison between XBF and Its Parental Lineages - Fabio Scarpa; Chiara Locci; Ilenia Azzena; Marco Casu; Pier Luigi Fiori; Alessandra Ciccozzi; Marta Giovanetti; Miriana Quaranta; Giancarlo Ceccarelli; Stefano Pascarella; Massimo Ciccozzi; Daria Sanna (Microorganisms, 2023)
Recombination events are very common and represent one of the primary drivers of RNA virus evolution. The XBF SARS-CoV-2 lineage is one of the most recently generated recombinants during the COVID-19 pandemic. It is a recombinant of BA.5.2.3 and BA.2.75.3, both descendants of lineages that caused many concerns (BA.5 and BA.2.75, respectively). Here, we performed a genomic survey focused on comparing the recombinant XBF with its parental lineages to provide a comprehensive assessment of the evolutionary potential, epidemiological trajectory, and potential risks. Genetic analyses indicated that although XBF initially showed the typical expansion depicted by a steep curve, causing several concerns, currently there is no indication of significant expansion potential or a contagion rate surpassing that of other currently active or previously prevalent lineages. BSP indicated that the peak has been reached around 19 October 2022 and then the genetic variability suffered slight oscillations until early 5 March 2023 when the population size reduced for the last time starting its last plateau that is still lasting. Structural analyses confirmed its reduced potential, also indicating that properties of NTDs and RBDs of XBF and its parental lineages present no significant difference. Of course, cautionary measures must still be taken and genome-based monitoring remains the best tool for detecting any important changes in viral genome composition.